Appendiceal and bowel endometriosis mimicking acute appendicitis with small bowel obstruction: case report and brief review of the literature - Palomares-Leal, Alain; Morales Cardona, Antonio; Perez-Macias, Jorge Pablo; Peña, Danilo Tueme-De La; Sifuentes-Gallardo, Rogelio Alejandro; Curz, Carla Paulina Campos (International Surgery Journal, 2023)
Endometriosis is defined as the presence of endometrium-like tissue outside the uterine cavity. This disease can have a variable presentation with symptoms that range from asymptomatic to non-menstrual pelvic pain, dysmenorrhea, dyspareunia, bowel symptoms, infertility, among others. We hereby present the case of a 39-year old female that presented to emergency room complaining of abdominal pain in right iliac fossa. Acute appendicitis was suspected, even though CT scan was inconclusive. Diagnostic laparoscopy was scheduled and laparoscopic appendectomy was performed and pathology examination reported acute appendicitis due to appendiceal endometriosis.